STRATEGI BADAN PERTANAHAN NASIONALDALAM MENCEGAH DAN MENYELESAIKAN KONFLIK PERTANAHAN:STUDI DI KANTOR BADAN PERTANAHAN NASIONAL KOTA PALANGKA RAYA - Desy Frisutami (Journal Ilmu Sosial, Politik dan Pemerintahan, 2016)
Conflict over land is a problem that can not be ignored and must be addressed because of land conflict is potentially a social conflict in the community, so it takes strategy in the prevention and resolution. In the town of Palangka Raya there is some conflict-prone areas of land that requires serious treatment of the agency having authority in the land secto. The purpose of this study is to describe and analyze the strategies of the National Land Agency in preventing and resolving conflict over land as well as the challenges and success factors in implementing the strategy of prevention and settlement of land disputes. With the research methods descriptive qualitative is to portray the state of the object and the subject under study based on the facts in the field by conducting observation and interview.Based on these results the National Land Agency strategies town of Palangka Raya in preventing conflict over land is by providing counseling / dissemination to the public, control of land administration both juridical and field, provide information quickly and accurately, and to empower them with various programs. As for the completion strategy there are several stages of assessment of conflict-related data juridical and physical data, subsequent handling of the conflict by means of mediation both parties to hold meetings / consensus. And the last is the settlement of land disputes is the final stage of the National Land Agency Palangka Raya city tried to lead with both sides in order to find an agreement towards peace so problems not up to court three times mediation. Of the strategy can be said of the remedies is maximal and can realize a land policy for justice and the welfare of society as there are some issues of land that has been able to be solved by consultation / consensus without having to be brought to court.Expectations of the future National Land Agency of the city of Palangka Raya prioritize prevention compared finish because it would be better if it did not appear the land issue. Then tighten their enforcement in the administration because the administration is mistaken as a double certificate is one of the causes of land conflicts.